Phage Therapy Against Biofilm of Multidrug-Resistant Klebsiella Pneumoniae Isolated from Zakho Hospital Samples - Yousif Abdullah AlBany; Mohammad Ismail Al-Berfkani; Mahde Saleh Assaf (Polytechnic Journal)
Klebsiella pneumoniae causes infection in human, especially in immunocompromised patients. About 80% of nosocomial infection caused by K. pneumoniae is due to multidrug-resistant strain. The emergence of antibiotic-resistant bacterial strains necessitates the exploration of alternative antibacterial therapies, which led to studying the ability of viruses that infect the bacteria (known as bacteriophage) to treat infection with K. pneumoniae. Bacterial biofilm which are crucial in the pathogenesis of much clinically important infection and are difficult to eradicate because they exist resistant to many antimicrobial treatment. Biofilm formation by K. pneumoniae is responsible for the catheter associated infection such as urinary tract infection and respiratory tract infection due to the colonization of the polymeric surface by forming multilayered cell cluster embedded in extracellular materials. In this study K. pneumoniae isolated from the hospital environment and characterized it and form the biofilm of that organism by microplate quantitative assay. Similarly bacteriophage specific for K. pneumoniae isolated from river water. The aim of work is the use of bacteriophage as a possible alternative for the treatment of bacterial infection of K. pneumoniae. We showed that biofilm is reduced by isolated phages by the comparative account of colony-forming unit versus plaque-forming unit. The result of this study, therefore, suggests that the timing of starting the phage therapy after initiation of infection significantly contributes toward the success of the treatment.